Determinanty opłacalności inwestycji na rynku nieruchomości mieszkaniowych - Gawron, Henryk (Determinants of Investment Profitability in the Residential Real Estate Market, 2008)
Nowadays, one of the most important tasks for every investor in the real estate market is define and calculate investment risk, as well as taking different tasks and decisions how to minimize the risk in the investment process management. Major risk factors and causes of investment project failure are: too optimisticly or not precisely stated goals at the first stage of investment process, insufficient studies in the field of the future demand size and structure in the local real estate market, bad investment location, unsuccessful functional designs, option of the inappropriate project financing method, the lack of professionalism, according to the investment team, problems at the stage of investment project realization
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 181-188